Ecofriendly synthesis and solar photocatalytic activity of S-doped ZnO - Patil, Ashokrao B.; Patil, Kashinath R.; Pardeshi, Satish K. (Journal of Hazardous Materials, 2010)
The S-doped ZnO was prepared by new ecofriendly method, which involves simple mechanochemical synthesis followed by thermal decomposition of bisthiourea zinc oxalate (BTZO) powders. The BTZO was characterized by FTIR and TG-DTA analysis while S-doped ZnO crystallite was characterized by XRD, XPS, SEM, EDXS, and photoluminescence (PL) spectra. X-ray diffraction data suggest the single phase wurtzite structure for S-doped ZnO and the incorporation of sulfur expand the lattice constants of ZnO. Room temperature PL spectra show more number of oxygen vacancies in S-doped ZnO as compare to that of pure ZnO. Photocatalytic activity of S-doped ZnO was checked by means of solar photocatalytic degradation (PCD) of resorcinol, using a batch photoreactor. The PCD efficiency of S-doped ZnO was found to be 2 times greater than that of pure ZnO. The inherent relationship between PL intensity and photocatalytic activity of S-doped ZnO was discussed. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Photocatalysis; photoluminescence; Resorcinol; S-doped ZnO; Sunlight; XPS

Efficiency and recycling capability of montmorillonite supported Fe-Ni bimetallic nanocomposites towards hexavalent chromium remediation - Kadu, Brijesh S.; Sathe, Yogesh D.; Ingle, Abhijit B.; Chikate, Rajeev C.; Patil, Kashinath R.; Rode, Chandrashekhar V. (Applied Catalysis B-Environmental, 2011)
The remediation of Cr(VI) from simulated water streams is investigated using Fe-Ni bimetallic nanoparticles (Fe-Ni NPs) and their nanocomposites prepared with montmorillonite (MMT) clay. These nanocomposites are characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and Brunauer-Emmett-Teller (BET) surface area analyses. XRD analysis revealed proper dispersion as well as intercalation of Fe-Ni NPs in the clay matrix. TEM of nanocomposites showed the presence of spherical particles having a size of 20-40 nm. Batch experiments with a 25 mg L(-1) Cr(VI) solution and 2 g L-1 Fe-Ni NPs exhibited complete reduction of Cr(VI) within 10 min that follows first order reaction kinetics. Amongst 25%, 50%, 75% in situ and loaded nanocomposites, 75% compositions possess better activity with enhanced reduction capacity below pH 4 due to generation of reactive H center dot species. XPS analysis of nanocomposites after Cr(VI) treatment suggested that reduction process occurs through Cr(111) formation followed by its subsequent reduction to Cr(0). Their potentiality towards reusage is established from the recycling experiments that revealed the order of efficiency as 75% in situ > Fe-Ni NPs > 75% loaded nanocomposites. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Cr(VI) remediation; Iron-nickel bimetallics; Montmorillonite; Nanocomposites; Recycling

Enhancement of oxygen vacancies and solar photocatalytic activity of zinc oxide by incorporation of nonmetal - Patil, Ashokrao B.; Patil, Kashinath R.; Pardeshi, Satish K. (Journal of Solid State Chemistry, 2011)
B-doped ZnO and N-doped ZnO powders have been synthesized by mechanochemical method and characterized by TG-DTA, XRD, SEM-EDX, XPS, UV-visible and photoluminescence (PL) spectra. X-ray diffraction data suggests the hexagonal wurtzite structure for modified ZnO crystallites and the incorporation of nonmetal expands the lattice constants of ZnO. The room temperature PL spectra suggest more number of oxygen vacancies exist in nonmetal-doped ZnO than that of undoped zinc oxide. XPS analysis shows the substitution of some of the O atoms of ZnO by nonmetal atoms. Solar photocatalytic activity of B-doped ZnO, N-doped ZnO and undoped ZnO was compared by means of oxidative photocatalytic degradation (PCD) of Bisphenol A (BPA). B-doped ZnO showed better solar PCD efficiency as compare to N-doped ZnO and undoped ZnO. The PCD of BPA follows first order reaction kinetics. The detail mechanism of PCD of Bisphenol A was proposed with the identification of intermediates such as hydroquinone, benzene-1,2,4-triol and 4-(2-hydroxypropan-2-yl) phenol. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Bisphenol A; Enhanced oxygen vacancies; Nonmetal doping; Photocatalysis; Sunlight

Enhanced electrochromic coloration in Ag nanoparticle decorated WO3 thin films - Kharade, Rohini R.; Mali, Sawanta S.; Patil, Satish P.; Patil, Kashinath R.; Gang, Myong G.; Patil, Pramod S.; Kim, Jin H.; Bhosale, Popatrao N. (Electrochimica Acta, 2013)
WO3/Ag composite thin films were prepared by microwave assisted sol-gel synthesis (MW-SGS) of WO3 followed by vacuum evaporation of Ag nanoparticles and their enhanced electrochromic coloration was investigated. The composition and morphology of WO3 thin films with different thickness of Ag layer obtained by vacuum evaporation were investigated. Distinct plasmon absorption bands of Ag nanoparticle thin films were obtained. The optical band gap energy of WO3/Ag films decreased with increasing the Ag layer thickness. The surface of these films has been examined using X-ray photoelectron spectroscopy (XPS) to gain information about the chemical states of species present at surfaces. Experimental results indicated that the conductivity of the films increased after surface modification by Ag layer. To investigate the origin of enhanced electrochromic absorption in optical properties, working electrode consisting of WO3/Ag thin film was used and observed the optical properties during electrochemical reaction. It was found that composite electrode shows enhancement in electrochromic properties in terms of optical modulation (Delta OD) and coloration efficiency (eta). (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Ag2WO4; CIE coordinates; Electrochromism; SPR; WO3/Ag composite thin films